Uses and gratifications of social media in the Middle East North Africa region - Taha, Yousra Osama (AUC Knowledge Fountain, 2020)
This study explores the relation between the adoption of various social media platforms and the demographic variables of users consuming these platforms in the Middle East and North Africa (MENA) region. It also provides a better understanding of the positive and negative gratifications acquired when users adopt social media in the region. The uses and gratifications (U&G) perspective is the theoretical grounding of the study applied to newer media, social media platforms in specific. A quantitative questionnaire, conducted within the social media users whose home countries are from the MENA region (N=561) to indicate the behavior of social media adoption in relation to 8 motivation variables. Three in-depth interviews were also conducted to analyze the findings and result, presenting insights on the assumed hypotheses. Findings of the study showed that there's a significant relation between using social media and the use of media utilities in terms of content creation and content engagement. It also showed that social media delivered not only positive gratifications, but also negative ones. Users may gain better online social activity, online learning opportunities, online active citizenship and online efficiency, but on the other hand, they also risk personal privacy violations, social media addiction, and distractions from daily tasks.